2017
DOI: 10.1186/s40249-017-0283-5
|View full text |Cite
|
Sign up to set email alerts
|

Malaria elimination in Lao PDR: the challenges associated with population mobility

Abstract: Although the Lao People’s Democratic Republic (Lao PDR) is comparatively small landlocked country with patterns of both in- and out-migration, its human migration situation has been poorly studied. This is despite all of the country’s 18 provinces sharing both official and unofficial border checkpoints with neighboring countries. Economic reforms in the last decade have seen a gradual increase in the promotion of foreign investment, and main towns and transportation networks have been expanding thus offering n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 9 publications
3
72
0
Order By: Relevance
“…In total, sixty-three percent of the vector were collected outdoors which is in adequacy with the results of Malaria transmission in the Mekong region is currently concentrated in forested and rural areas and along national borders from where the disease is likely to spread to other areas due to the movement of population groups (WHO 2019, Kounnavong et al, 2017;Inthavong et al, 2017). A part of the transmission is taking place outdoors in the villages as previously mentioned, but the remaining transmission occurs outside of the villages, especially in the forest.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In total, sixty-three percent of the vector were collected outdoors which is in adequacy with the results of Malaria transmission in the Mekong region is currently concentrated in forested and rural areas and along national borders from where the disease is likely to spread to other areas due to the movement of population groups (WHO 2019, Kounnavong et al, 2017;Inthavong et al, 2017). A part of the transmission is taking place outdoors in the villages as previously mentioned, but the remaining transmission occurs outside of the villages, especially in the forest.…”
Section: Discussionmentioning
confidence: 56%
“…Despite a continued decline of malaria cases (by 74%) and deaths (by 94%) in the last decade in the Greater Mekong Subregion (GMS), malaria remains a major public health problem impacting on the health and lives of a large proportion of people particularly in remote areas and concentrated along international borders (Hii et al, 2018;Cui et al, 2018. In Laos, malaria transmission is heterogeneous, with more intense transmission in forested areas particularly in the southern part of the country (Kounnavong et al 2017) where more than 207,000 cases were reported in 2018. The country has implemented a nation-wide malaria control program since 1992, and the current strategies emphasize the promotion of long-lasting insecticide treated bed nets (LLINs), early diagnosis by microscopic examination and rapid diagnostic tests, and prompt treatment with artemisinin-based combination therapy (ACT).…”
Section: Introductionmentioning
confidence: 99%
“…The broader social environment in which a migrant lives, works and interacts is a significant determinant of health and health inequities in the Western Pacific Region. In the Lao People's Democratic Republic, for example, malaria is most prevalent in the southern parts of the country, where many communities are engaged in forest-related work (83). Unregulated deforestation, land clearing for development projects and changes in climate conditions have all been linked to an increased risk of exposure (83).…”
Section: Broader Social Determinantsmentioning
confidence: 99%
“…In the Lao People's Democratic Republic, for example, malaria is most prevalent in the southern parts of the country, where many communities are engaged in forest-related work (83). Unregulated deforestation, land clearing for development projects and changes in climate conditions have all been linked to an increased risk of exposure (83). A report of an outbreak in 2011 suggested internal and cross-border migrants accounted for 70% of confirmed malaria cases in the Lao People's Democratic Republic (83).…”
Section: Broader Social Determinantsmentioning
confidence: 99%
See 1 more Smart Citation